A Comparative Study on Knowledge Level of Climate Smart Agricultural Practices (CSAP) among Paddy Farmers in Eastern Haryana (Indian Journal of Extension Education, 2024)
Climate-smart agricultural practices (CSAP) are an integrated approach that focuses on attaining triple objectives of increasing productivity, enhancing resilience, and reducing greenhouse gas emissions. The study was conducted in 2024 to assess the knowledge level of climate smart agricultural practices among the paddy growers of Haryana. The data was collected with a structured interview schedule from two groups of villages namely climate smart villages (CSV) and non-climate smart villages (N-CSV), randomly selected from four blocks of Karnal and Kaithal districts. A sample of 15 paddy farmers were randomly interviewed from each of the eight villages, thereby using a sample size of 120 respondents. The knowledge items were divided into five categories, namely water smart, nutrient smart, carbon smart, weather smart and knowledge smart as per FAO guidelines. The analysis found a considerable difference in the knowledge level of CSAP among CSV and N-CSV respondents. The knowledge index of farmers from CSV was higher than those from N CSV for all five dimensions of CSAP. Further, it was found that variables such as education, extension participation, social participation, economic motivation, scientific and risk orientation were all positively and significantly related to the knowledge index of farmers.